2006
DOI: 10.1016/j.plaphy.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum targeted GFP reveals ER organization in tobacco NT-1 cells during cell division

Abstract: The endoplasmic reticulum (ER) of plant cells undergoes a drastic reorganization during cell division. In tobacco NT-1 cells that stably express a GFP construct targeted to the ER, we have mapped the reorganization of ER that occurs during mitosis and cytokinesis with confocal laser scanning microscopy. During division, the ER and nuclear envelope do not vesiculate. Instead, tubules of ER accumulate around the chromosomes after the nuclear envelope breaks down, with these tubules aligning parallel to the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 48 publications
3
34
0
1
Order By: Relevance
“…This would result in chromatin-bound ER and/or NE cisternae becoming trapped in the interstitial space giving the impression of NR development (Gupton et al, 2006). However, it has been shown that NR can develop without mitosis (Fischer et al, 2003), persist throughout interphase (Fricker et al, 1997b;Olins and Olins, 2009) and specific cell types display heritable patterns (Fricker et al, 1997b), which strongly suggests physiological regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This would result in chromatin-bound ER and/or NE cisternae becoming trapped in the interstitial space giving the impression of NR development (Gupton et al, 2006). However, it has been shown that NR can develop without mitosis (Fischer et al, 2003), persist throughout interphase (Fricker et al, 1997b;Olins and Olins, 2009) and specific cell types display heritable patterns (Fricker et al, 1997b), which strongly suggests physiological regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Tubules of ER were observed to accumulate around the chromosomes after nuclear-envelope breakdown, with the tubules aligned parallel to the microtubules of the mitotic spindle. In cytokinesis, the phragmoplast becomes enriched in ER, and this redistribution appears to be microtubule dependent (Gupton et al, 2006). Similarly, in mammalian cells, the ER is aligned around the contours of the spindle body and oriented along microtubules (McCullough and Lucocq, 2005) (Fig.…”
Section: The Role Of the Er In Cytokinesismentioning
confidence: 91%
“…Recent studies have also hinted at a role for the ER in cytokinesis. Studies that used GFP-tagged ER-resident proteins in plant cells have revealed that the ER undergoes pronounced reorganisation during mitosis and cytokinesis (Gupton et al, 2006). Tubules of ER were observed to accumulate around the chromosomes after nuclear-envelope breakdown, with the tubules aligned parallel to the microtubules of the mitotic spindle.…”
Section: The Role Of the Er In Cytokinesismentioning
confidence: 99%
“…We should caution, however, that this by no means excludes a role for microtubules exerting a regulating influence on the dynamics of the ER at other stages of the cell cycle. Indeed, it is quite likely that during the transition to metaphase, while the nuclear envelope resorbs into the ER, which then forms aggregates at the spindle poles, there is a switch over from an actin-based movement to microtubule-based movement on spindle microtubules (Gupton et al, 2006). The association of ER membrane with spindle microtubules in plants is well established (Hepler and Wolniak, 1984).…”
Section: The Effect Of the Actomyosin System And Microtubules On Er Rmentioning
confidence: 99%